Residual force enhancement contributes to increased performance during stretch-shortening cycles of human plantar flexor muscles in vivo - Hahn, D.; Riedel, T. N. (Journal of Biomechanics, 2018)
It is well known that muscular force production is history-dependent, which results in enhanced (RFE) and depressed (RFD) steady-state forces after stretching and shortening, respectively. However, it remains unclear if force-enhancing mechanisms can contribute to increased performance during in vivo stretch-shortening cycles (SSCs) of human locomotor muscles. The purpose of this study was to investigate whether RFE-related mechanisms contribute to enhanced force and power output during SSCs of the human plantar flexor muscles. Net ankle torques of fourteen participants were measured during and after pure isometric, pure stretch, pure shortening, and SSC contractions when the triceps surae muscles were electrically stimulated at a submaximal level that resulted in 30% of their maximum isometric torque. Dynamic contractions were performed over an amplitude of 15°, from 5° plantar flexion to 10° dorsiflexion, at a speed of 120° s-1. External ankle work during shortening was 11.6% greater during SSCs compared to pure shortening contractions (p = .003). Additionally, RFD after SSCs (8.6%) was reduced compared to RFD after pure shortening contractions (12.0%; p < .05). It is therefore concluded that RFE-related mechanisms contribute to increased performance following SSCs of human locomotor muscles. Since RFD after SSCs decreased although work during shortening was increased, we speculate that the relevant mechanism lies outside actin-myosin interaction. Finally, our data suggests that RFE might be relevant and beneficial for human locomotion whenever a muscle is stretched, but this needs to be confirmed.